4′-phosphopantetheine acts as a potential antioxidant to limit atherosclerotic plaque formation by inhibiting ROS generation - Zhai, Taiyu; Ren, Wenbo; Wang, Pingping; Hu, Xiumei; Wang, Jingyu; Zheng, Lei (Frontiers in Physiology, 2022)
Coronary heart disease (CHD) is caused by coronary atherosclerosis and has high morbidity and mortality rate worldwide. There are challenges in both early screening and treatment of CHD. CHD occurrence and development is a complex metabolic disorder process. Therefore, to search for novel biomarkers of CHD, we analyzed the peripheral blood metabolome in CHD patients. In the study, a plasma metabolite, 4’-Phosphopantetheine (4-PPanSH), which was discovered by HPLC-MS/MS, as the peripheral blood 4-PPanSH decreases, the degree of coronary blockage gradually aggravates. Also, supplement 4-PPanSH limited atherosclerotic plaque formation and endothelial injury in mice. And in vascular endothelial cells, 4-PPanSH effectively inhibited ROS generation and ox-LDL accumulation. In summary, 4-PPanSH was associated with the degree of coronary stenosis, and supplement 4-PPanSH reduced atherosclerotic plaque generation, which could be associated with 4-PPanSH act as a potential antioxidant inhibiting ROS generation and alleviating vascular endothelial injury.